2012
DOI: 10.3109/0142159x.2012.731104
|View full text |Cite
|
Sign up to set email alerts
|

Personality types and specialist choices in medical students

Abstract: Different personality types have distinct preferences in medical students' choice of careers. Personality and specialty choice research can enhance career counselling of medical students and fresh graduates. This also has implications for predicting the specialty distribution of the future health careers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
2
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 29 publications
1
38
2
5
Order By: Relevance
“…Mehmood et al [14] grouped anaesthesiology with hospital-based procedures, whereas we grouped it with surgical specialties.…”
Section: Study Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mehmood et al [14] grouped anaesthesiology with hospital-based procedures, whereas we grouped it with surgical specialties.…”
Section: Study Limitationsmentioning
confidence: 99%
“…A study of 590 medical students in Saudi Arabia, [14] using the ZKPQ, found that those interested in surgical specialties scored higher than all other specialty choice groups on all factors, including neuroticism-anxiety, except for activity.…”
Section: Consulting Group V Surgical Groupmentioning
confidence: 99%
“…In this study, we focused on an instrument of which the English version has been used in the Arabic medical education context by Mehmood et al (2013), namely the ZuckermanKuhlman Personality Questionnaire. Considering the disadvantages of using non-native questionnaires (Gibbons et al 1999;Harzing 2006), however, it seems better to use native questionnaires.…”
Section: Practice Pointsmentioning
confidence: 99%
“…O ponto de partida para solucionar essas questões é o conhecimento sobre o processo de escolha da especialidade e seus múltiplos condicionantes 5,9 . Estes têm sido agrupados em fatores externos e internos 9,10 . Entre os primeiros, destacam--se mercado de trabalho, retorno financeiro e disponibilidade de programas de residência 1,10,11 .…”
unclassified
“…Estes têm sido agrupados em fatores externos e internos 9,10 . Entre os primeiros, destacam--se mercado de trabalho, retorno financeiro e disponibilidade de programas de residência 1,10,11 . Entre os fatores internos, descrevem-se aqueles relacionados com interesses, aptidões e valores do responsável pela escolha 1,10,11 , que parecem ter papel predominante 12,13 .…”
unclassified